Peranan Hakim Pengawas dan Pengamat dalam Pembinaan Narapidana - Sarah, Putri; Liyus, Herry; Munandar, Tri Imam (PAMPAS: Journal of Criminal Law, 2021)
This study aims to understand and determine the implementation of the duties of supervisory judges and observers in fostering female prisoners in Class II B Women's Prison in Jambi. To understand and know the supervisor and observer judges in the development of female prisoners in Class II B Women's Prison in Jambi. The results obtained in this study show that the implementation of the duties of supervisory judges and observers in fostering female prisoners at Class II B Women's Prison in Jambi is to ensure that judges' decisions are carried out according to law. The contribution of supervisory judges and observers in fostering female prisoners at the Class II B Women's Prison in Jambi ensures that the rights of female prisoners are protected in accordance with Article 14 of the Correctional Law. Â  ABSTRAK Penelitian ini bertujuan untuk memahami dan mengetahui pelaksanaan tugas hakim pengawas dan pengamat dalam pembinaan narapidana wanita di Lapas Perempuan Kelas II B Jambi. Untuk memahami dan mengetahui hakim pengawas dan pengamat dalam pembinaan narapidana wanita di Lapas Perempuan Kelas II B Jambi. Hasil Penelitian yang diperoleh dalam penelitian ini bahwa pelaksanaan tugas hakim pengawas dan pengamat dalam pembinaan narapidana wanita di Lapas Perempuan Kelas II B Jambi yakni memastikan putusan hakim dilaksanakan sesuai undang-undang. Adapun kontribusi hakim pengawas dan pengamat dalam pembinaan narapidana wanita di Lapas Perempuan Kelas II B Jambi memastikan hak-hak narapidana wanita terlindungi sesuai pasal 14 UU Pemasyarakatan.